5th International Conference on Imaging for Crime Detection and Prevention (ICDP 2013) 2013
DOI: 10.1049/ic.2013.0258
|View full text |Cite
|
Sign up to set email alerts
|

Age Prediction from Iris Biometrics

Abstract: This paper proposes and investigates experimentally an approach to age prediction from iris images by using a combination of a small number of very simple geometric features, and a more versatile and intelligent classifier structure which can achieve accuracies to 75%. To our knowledge, this is the first experimental study of three class age prediction from iris images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Just like physical shape, skin texture, and cognitive abilities, human eyes and visual behavior are fundamentally affected by the aging process [20,36]. For example, eye tracking studies found age-related differences in people's visual explorativeness, pupil reactions to certain visual stimuli, and error rates in eye movement tasks [36,42].…”
Section: Age and Gender Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like physical shape, skin texture, and cognitive abilities, human eyes and visual behavior are fundamentally affected by the aging process [20,36]. For example, eye tracking studies found age-related differences in people's visual explorativeness, pupil reactions to certain visual stimuli, and error rates in eye movement tasks [36,42].…”
Section: Age and Gender Recognitionmentioning
confidence: 99%
“…Dynamic facial expressions, such as smiles, may also be analyzed to infer the age of test subjects [17]. Other parameters utilized for computerized age-group recognition include iris size and iris texture [20].…”
Section: Age and Gender Recognitionmentioning
confidence: 99%
“…[16, 18, 19]. Previously, near‐infrared (NIR) iris images for age estimation were employed, taking advantage of available iris databases [61, 62]. These studies used geometric or textural information, attaining an accuracy of ∼64%.…”
Section: Related Work On Age and Gender Classification Using Ocular Imagesmentioning
confidence: 99%
“…Other biometric modalities have received rather less attention from the research community; however, investigations can be found for age prediction using modalities such as the handwritten signature [103,104]. The investigation of age prediction from gait data can be found in [44,105], while [46,106] investigate the prediction of age from iris data using different sets of geometric and texture features. In [45,100,107], the authors have investigated the prediction of age from voice data, and Merkel et al [108] examines the prediction of subject age from the fingerprint.…”
Section: Age Estimationmentioning
confidence: 99%